2021
DOI: 10.1038/s41598-021-92379-6
|View full text |Cite
|
Sign up to set email alerts
|

A rapid phenotype change in the pathogen Perkinsus marinus was associated with a historically significant marine disease emergence in the eastern oyster

Abstract: The protozoan parasite Perkinsus marinus, which causes dermo disease in Crassostrea virginica, is one of the most ecologically important and economically destructive marine pathogens. The rapid and persistent intensification of dermo in the USA in the 1980s has long been enigmatic. Attributed originally to the effects of multi-year drought, climatic factors fail to fully explain the geographic extent of dermo’s intensification or the persistence of its intensified activity. Here we show that emergence of a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…raises the question about the existence of specific strains. For example, such specific strain was recently highlighted for Perkinsus marinus with the emergence between 1983 and 1990 of a new hypervirulent phenotypic strain that includes a shortened life cycle and a trophism shift from deeper connective tissues to digestive epithelia ( Carnegie et al, 2021 ). Authors hypothesized that the development of this new strain may be related to reduced oyster abundance and the rapid establishment of the exotic parasite H. nelsonii in 1959.…”
Section: Introductionmentioning
confidence: 99%
“…raises the question about the existence of specific strains. For example, such specific strain was recently highlighted for Perkinsus marinus with the emergence between 1983 and 1990 of a new hypervirulent phenotypic strain that includes a shortened life cycle and a trophism shift from deeper connective tissues to digestive epithelia ( Carnegie et al, 2021 ). Authors hypothesized that the development of this new strain may be related to reduced oyster abundance and the rapid establishment of the exotic parasite H. nelsonii in 1959.…”
Section: Introductionmentioning
confidence: 99%
“…The increased rate of disease spread in the southern latitudes suggests that environmental conditions either increased host susceptibility and/or disease transmission, or that genetic variability in the host or disease leads to a higher transmission rate (e.g. [ 35 ]). It will be difficult to disentangle these possibilities until a causative agent of SSWD has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…If true, the susceptibility and heavy mortality observed in C. virginica may be caused by recently increased virulence of P. marinus during the coevolutionary race between the host and parasite ( Van Valen, 1973 ). It has been suggested that increased virulence possibly associated with warm winters due to global warming played major roles in outbreaks and northward range extension of P. marinus ( Ford, 1996 ; Carnegie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%